Enhancement of tunnel ventilation and safety measures using PLC and SCADA for train movement - Davidson Kamaladhas, M.; Anitha, P.; Karthikeyan, K.; Amosedinakaran, S. (Journal of the Chinese Institute of Engineers, 2025)
The tunnel ventilation technique is gaining a lot of interest due to the emergence of new technologies that can be implemented inside the tunnel. In this paper, portal-to-shaft and shaft to shaft type of ventilation, artificial ventilation principle, transverse type of system, and fire safety measures are implemented, discussed, and examined. Thus, including these types and principles the system is developed effectively to operate under certain conditions. So, to automate the tunnel programmable logic controllers (PLC) and supervisory control and data acquisition (SCADA) are interfaced for monitoring and controlling purposes. The PLC opted is DELTA for which the code is written in Ladder language using WPLSoft software (according to the conditions mentioned) and SCADA is designed in InTouch software (with the help of tag generation). Arduino with a driver circuit is also implemented to drive the motor and the code is written in C language. The whole system communicates data to SCADA by RS232 serial communication using Modbus protocol. This proposed system was successfully tested which resulted in communication between the interfaced devices. The result of the study has enabled the automation of interfaced devices to detect and be aware of the comprehensive status of the tunnel.